Studyng the effects of Cantharellus cibarius fungi on Opisthorchis felineus trematode and on parasite host - C57BL/6 inbred mice - M. A. Tsyganov; G. B. Vishnevetskaya; T. P. Kukina; I. V. Sorokina; M. N. Lvova; M. A. Protsenko; N. E. Kostina; D. F. Avgustinovich (Вавиловский журнал генетики и селекции)
Opisthorchiasis is a dangerous parasitic disease caused by trematodes in the family Opisthorchiidae. One of the causes of this infection is the species Opisthorchis felineus, which is common in the Russian Federation and Western Europe. The disease has a large number of complications and relatively few effective treatments, so nowadays it is relevant to look for new drugs for the treatment of opisthorchiasis, with the maximum antiparasitic and minimal side effect. In this work, a potentially anthelmintic effect of the methanol extract of the golden chanterelle mushroom (Cantharellus cibarius) was investigated. In in vitro experiments, the significantly reduced mobility and survival rates of juvenile O. felineus specimens with increasing concentrations (10-1000 pg/ml) of the C. cibarius extract were shown. In in vivo studies, administration of the C. cibarius extract on the first day after parasitic infection of inbred C57BL/6 mice resulted in a decrease of the number of helminths in the bile ducts of the liver, evaluated 6 weeks after infection. In another series of experiments, administration of the C. cibarius extract for 7 days to mice infected with O. felineus for five weeks had no anthelmintic effect. In both cases, the state of the infected hosts, evaluated by a number of physiological and biochemical parameters (relative weight of organs, blood indices), did not deteriorate, indicating that there was no adverse effect of the C. cibarius extract. The results obtained suggest that the C. cibarius extract might have anthelmintic properties if applied as parasite larvae excyst.